Navigating Complex Realities: Barriers to Health Care, Law Enforcement and Mental Health Concerns of Undocumented African Immigrant Women in the United States - (:unkn) unknown (My University, 2018)
It is well established that undocumented immigrants experience structural barriers to accessing resources and services including healthcare. Existing literature largely examines the experiences of undocumented Latino immigrants. To address this gap, the qualitative descriptive study was conducted to understand undocumented African immigrant women’s barriers to healthcare access, their experiences seeking healthcare within a racialized context and how the complex stressors they face impact their health and well-being. This study was undergirded by a postcolonial feminist framework. Twenty-four undocumented African immigrant women and twenty nurses were interviewed about their perceptions of barriers to healthcare access for undocumented immigrants. Data were collected using in-depth, semi-structured interviews and analyzed using thematic analysis. The findings derived from interviews with the women centered around one major theme navigating complex realities. The three data-based manuscripts generated from this study further elaborate on the idea that undocumented African women were tasked with navigating barriers to accessing health care, navigating bias within various institutions and coping with the impact of their complex realities on their emotional well-being. The findings of this study contribute important knowledge to our understanding of the barriers that undocumented African women experience when seeking healthcare and when in need of law enforcement services to ensure their safety. Findings also reveal the mental health concerns of undocumented African women. Deconstruction of the experiences of undocumented African women is an essential component in learning how to create safe spaces and in driving impactful social change.
Keywords: African immigrants; Immigrants' health; Postcolonial feminism; Undocumented immigrants